FRI0375 A Delphi Exercise for Treatment Algorithms for Systemic Lupus Erythematosus. (10th June 2014) - Muangchan, C.; Pope, J.E.
Abstract : Background: Treatment for SLE is often organ based. The literature lacks trials and consensus for treatment in SLE when standard first or second line care is ineffective. Objectives: To determine expert consensus for SLE treatment using case scenarios and especially for treatment beyond first line therapy. Methods: SLE experts (n=69) were sent three surveys; writing therapies for SLE organ complications assuming inadequate response to each choice and providing a list of secondary choices. Results: The response rate for the first survey where all treatment options were written by the experts was 54%. For each subsequent survey, the response rate decreased. For widespread DLE, first-line: topical steroids or tacrolimus+hydroxychloroquine (HCQ) ± glucocorticoids, then azathioprine (AZA) and switching to mycophenolate mofetil (MMF). For cutaneous vasculitis, first-line was GC ± HCQ ± methotrexate (MTX), followed by adding either AZA or MMF and then IV cyclophosphamide (CYC). For gangrenous vasculitis, first-line was glucocorticoids+CYC, then rituximab (RTX) or plasmapheresis and maintenance with AZA or MMF. For arthritis, first-line therapy was HCQ ± glucocorticoids; adding MTX and then RTX. For pericarditis refractory to NSAIDs, first-line was glucocorticoids ± HCQ, then adding AZA, MMF or MTX and then Belimumab (BLM) or RTX; and if needed pericardial window and/or aspiration. For ILD, induction was glucocorticoids+MMF or CYC, then RTX or IVIG; maintenance with AZA or MMF. For PAH, glucocorticoids+CYC or MMF+endothelin receptor antagonist, adding phosphodiesterase-5 inhibitor and then prostanoid and RTX. First-line therapy was anticoagulation ± HCQ for lupus associated antiphospholipid antibody syndrome. A direct thrombin inhibitor was second-line therapy for venous thrombosis, and adding low dose aspirin or another platelet aggregation inhibitor was a second-line option for arterial thrombosis. For mononeuritis multiplex, and CNS vasculitis, first-line induction was glucocorticoids+CYC followed by maintenance with AZA, or MMF and then RTX, IVIG or plasmapheresis. For LN type III/IV and V first-line was glucocorticoids+MMF, then adding RTX for LN type III/IV or switching to AZA, CYC or RTX for LN type V. Treatment algorithm for organ system involvements by systemic lupus erythematosus: Conclusions: Consensus for SLE treatment had variable agreement but some treatment consensus beyond first line therapy was obtained. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2541